Novel haloalkaliphilic methanotrophic bacteria: An attempt for enhancing methane bio-refinery. (1st February 2019) - Cantera, Sara; Sánchez-Andrea, Irene; Sadornil, Lidia J.; García-Encina, Pedro A.; Stams, Alfons J.M.; Muñoz, Raúl
Abstract: Methane bioconversion into products with a high market value, such as ectoine or hydroxyectoine, can be optimized via isolation of more efficient novel methanotrophic bacteria. The research here presented focused on the enrichment of methanotrophic consortia able to co-produce different ectoines during CH4 metabolism. Four different enrichments (Cow3, Slu3, Cow6 and Slu6) were carried out in basal media supplemented with 3 and 6% NaCl, and using methane as the sole carbon and energy source. The highest ectoine accumulation (∼20 mg ectoine g biomass −1 ) was recorded in the two consortia enriched at 6% NaCl (Cow6 and Slu6). Moreover, hydroxyectoine was detected for the first time using methane as a feedstock in Cow6 and Slu6 (∼5 mg g biomass −1 ). The majority of the haloalkaliphilic bacteria identified by 16S rRNA community profiling in both consortia have not been previously described as methanotrophs. From these enrichments, two novel strains (representing novel species) capable of using methane as the sole carbon and energy source were isolated: Alishewanella sp. strain RM1 and Halomonas sp. strain PGE1. Halomonas sp. strain PGE1 showed higher ectoine yields (70–92 mg ectoine g biomass −1 ) than those previously described for other methanotrophs under continuous cultivation mode (∼37–70 mg ectoine g biomass −1 ). The results here obtained highlight the potential of isolating novel methanotrophs in order to boost the competitiveness of industrial CH4 -based ectoine production. Highlights: First proof of concept of CH4 bioconversion into ectoine and hydroxyectoine. The haloalkaliphilic consortium used efficiently converted CH4 into ectoines. Two novel species capable of using CH4 as the sole carbon source were isolated. Halomonas sp. strain PGE1 accumulated high ectoine yields using CH4. This article boosts the competitiveness of industrial CH4 -based ectoine production.